Antiseptic solutions for skin preparation during central catheter insertion in neonates - Muhd Helmi, Muhd Alwi; Lai, Nai Ming; Rosternberghe, Hans; Ayub, Izzudeen; Mading, Emie (John Wiley & Sons, Ltd., 2021)
This is a protocol for a Cochrane Review (intervention). The objectives are as follows: To systematically evaluate the safety and efficacy of different antiseptic solutions in preventing CRBSI and other related outcomes in neonates with CVC.